2020
DOI: 10.1002/jmv.26057
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of norovirus GI.4 from children with acute gastroenteritis in Jambi, Indonesia, 2019

Abstract: Norovirus (NoV) is one of the most important viral causes of acute gastroenteritis (AGE) in children worldwide. Only a few studies have reported AGE with NoV‐positive in some cities in Indonesia. This study aimed to investigate the incidence and clinical characteristic of NoV infection, and also genotype distribution of NoV in children with AGE in Jambi, as the capital and the largest city of Jambi province, Indonesia. Stool samples were collected from children (≤15 years of age) with AGE at three participatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 42 publications
(113 reference statements)
2
9
0
Order By: Relevance
“…A recent meta-analysis found that the highest frequency of NoV infection occurred in infants less than 12 months of age [24]. A second study of hospitalized patients in Indonesia found the highest frequency of NoV infection in those under 24 months of age [34]. In a summary of 10 community-based birth cohort studies, NoV-associated AGE was relatively uncommon in infants under 6 months of age [25].…”
Section: Clinical Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations
“…A recent meta-analysis found that the highest frequency of NoV infection occurred in infants less than 12 months of age [24]. A second study of hospitalized patients in Indonesia found the highest frequency of NoV infection in those under 24 months of age [34]. In a summary of 10 community-based birth cohort studies, NoV-associated AGE was relatively uncommon in infants under 6 months of age [25].…”
Section: Clinical Epidemiologymentioning
confidence: 99%
“…Yet, birth cohort studies conducted in low-and middle-income countries have demonstrated that 66-90% of the children experienced at least one NoV infection and 30-70% experienced NoV-associated AGE in early childhood, with an estimated incidence for NoV-associated AGE of 14 to 66 per 100 child years [25]. Male predominance has been often reported [24,33], with the highest rates of NoV AGE during winter or rainy seasons [34][35][36].…”
Section: Clinical Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies estimated that worldwide, noroviruses may cause >1 million hospitalizations and up to 200,000 deaths annually in children <5 years old (Ahmed et al, 2014;Bányai et al, 2018). In Indonesia, norovirus gastroenteritis occurs sporadically in children with a prevalence of 15 to 61%, and hospitalization is often required for the patients (Hakim et al, 2018;Nirwati et al, 2019;Athiyyah et al, 2020;Wulandari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%